The ballad of Lucy Whipple - Cushman, Karen (New York : Harper Trophy, 1998)
In 1849, a twelve-year-old girl who calls herself Lucy is distraught when her mother moves the family from Massachusetts to a small California mining town, where Lucy helps run a rough boarding house and looks for comfort in books while trying to find a way to get "home."
Originally published: New York : Clarion Books, 1996.
008-012.
1030
Keywords: Frontier and pioneer life -- California -- Fiction; Family life -- California -- Fiction; California -- Gold discoveries -- Fiction